Software development: do good manners matter? - Destefanis, Giuseppe; Ortu, Marco; Counsell, Steve; Marchesi, Michele; Tonelli, Roberto (PeerJ PrePrints, 2015)
A successful software project is the result of a complex process involving, above all, people. Developers are the key factors for the success of a software development process, not merely as executors of tasks, but as protagonists and core of the whole development process. This paper investigates social aspects among developers working on software projects developed with the support of Agile tools. We studied 22 open source software projects developed using the Agile board of the JIRA repository. All comments committed by developers involved in the projects were analyzed and we explored whether the politeness of comments affected the number of developers involved and the time required to fix any given issue. Our results showed that the level of politeness in the communication process among developers does have an effect on the time required to fix issues and, in the majority of the analysed projects, it had a positive correlation with attractiveness of the project to both active and potential developers. The more polite developers were, the less time it took to fix an issue. In the majority of the analysed cases, the more developers wanted to be part of a project, the more they were willing to continue working on the project over time.
Keywords: social and human aspects; politeness; mining software repositories; issue fixing time; software development